SOSIALISASI TENTANG PROFESI DI BIDANG AKUNTANSI BAGI MAHASISWA UNIVERSITAS SINGAPERBANGSA KARAWANG - Nopiana, Medi; Ramdan, Nurul Amalia; Liana, Siska; Lukita, Carolyn (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2025)
Community service activities to introduce the profession in the field of Accounting are greatly needed, particularly for students of the Accounting Department, Faculty of Economics and Business, Universitas Singaperbangsa Karawang. Therefore, the community service team from Universitas Singaperbangsa Karawang took the initiative to organize an activity to introduce the profession. This activity was attended by 59 students of the university's Accounting Department. The activity was located at Campus 2, Universitas Singaperbangsa Karawang, on Tuesday, November 26, 2024. The method of implementing the activity applied the socialization method. This activity provides benefits to students of the Accounting Department of this university in the form of gaining new knowledge and insights into various professions in the field of Accounting, as well as motivating them to pursue their careers in the future in other Accounting professions besides Corporate Accountants. Suggestions for this activity in the future are to hold it continuously and target all students of the Accounting Department of this university so that information and knowledge about the Accounting profession are fully conveyed to students of the department.